Upaya Mahasiswa Membantu Anak dalam Meningkatkan Perilaku Hidup Bersih di Panti Asuhan Anak Liora Terang - Arum Septyaningrum; Bengkel Ginting (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Good development in an early childhood depends on the clean living behavior that is carried out. This clean living behavior starts from small things such as always washing hands with soap, throwing trash in its place, brushing teeth regularly, cutting fingernails and toenails regularly, and other small behaviors. However, there are many children who ignore clean living behavior because they still lack knowledge about cleanliness. In this second practical activity, a student majoring in Social Welfare, Faculty of Social and Political Sciences, University of North Sumatra provided assistance to children at the Liora Terang Orphanage to improve clean living behavior at the Liora Terang Children's Orphanage. The provision of assistance in this activity is by using social intervention methods in the science of social welfare in groups (Groupwork). The stages carried out are the intake case; assessment and intervention planning; member selectors; group development; and evaluation and termination. The purpose of this second practicum activity is to increase children's independence in clean living behavior in children at the Liora Terang Children's Orphanage.